-8z-(3z+6)=4-z

Simplify each term.

Apply the distributive property.

-8z-(3z)-1⋅6=4-z

Multiply 3 by -1.

-8z-3z-1⋅6=4-z

Multiply -1 by 6.

-8z-3z-6=4-z

-8z-3z-6=4-z

Subtract 3z from -8z.

-11z-6=4-z

-11z-6=4-z

Add z to both sides of the equation.

-11z-6+z=4

Add -11z and z.

-10z-6=4

-10z-6=4

Add 6 to both sides of the equation.

-10z=4+6

Add 4 and 6.

-10z=10

-10z=10

Divide each term in -10z=10 by -10.

-10z-10=10-10

Cancel the common factor of -10.

Cancel the common factor.

-10z-10=10-10

Divide z by 1.

z=10-10

z=10-10

Divide 10 by -10.

z=-1

z=-1

Solve for z -8z-(3z+6)=4-z